PENGARUH LINGKUNGAN KERJA FISIK DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT TELKOM PROPERTY JAKARTA - Fadila Riandi; Imbron (Journal of Research and Publication Innovation, 2025)
This research aims to analyze the influence of the physical work environment and work discipline on employee performance at PT Telkom Property Jakarta. The research method used in this research is quantitative. The population and sample in this study were 52, using the formula saturated sampling technique and collection using a questionnaire, data analysis techniques using linear regression analysis and hypothesis testing. The results of this research show: There is an influence between the physical work environment on employee performance at PT Telkom Porperty Jakarta, with a calculated t value of 5.012 > t table 2.009 or probability Sig 0.000 > 0.05, simple linear regression equation Y = 3.871 + 1.130 The correlation is 0.578 with a medium level of relationship, and the coefficient of determination shows an influence contribution of 34.4%. There is an influence between work discipline on employee performance at PT Telkom Porperty Jakarta, with a calculated t value of 6.540 > t table 2.009 or probability Sig 0.000 > 0.05, simple linear regression equation Y = -7.289 + 1.292 Strong relationship, and the coefficient of determination shows an influence contribution of 46.1% and the remaining 53.9%. There is an influence between the physical work environment and work discipline simultaneously on employee performance at PT Telkom Porperty Jakarta, with a value of Fcount 23.111 > Ftable 3.187 or probability Sig 0.000 < 0.05, multiple linear regression equation Y = -10.484 + 0.418 X1 + 1.013 X2 , the correlation result is 0.697 with a strong relationship level, and the coefficient of determination shows that jointly the contribution of the influence of the physical work environment and work discipline on performance is 48.5% and the remaining 51.5% is influenced by other factors